Efficacy and safety of three plant extracts based formulations of vagitories in the treatment of vaginitis: a randomized controlled trial - Kemal Durić; Selma Kovčić Hadžiabdić; Mahira Durić; Haris Nikšić; Alija Uzunović; Hurija Džudžević Čančar (Medicinski glasnik, 2020)
Aim: There are more and more herbal preparations that are used for the purpose of treatment and improvement of the clinical manifestation of vaginitis not only by patients themselves, but also by healthcare professionals. Plant species, St. John’s wort, chamomile, calendula, yarrow, shepherd’s purse and tea tree oil are all well known for their anti-inflammatory, antimicrobial and wound healing activity. This paper presents the results of a clinical study in which three herbal formulations/vagitories, based on extracts of St. John’s wort, chamomile, calendula, yarrow, shepherd’s purse and tea tree oil, were investigated for their effectiveness on vaginitis. Methods: This was a randomized controlled clinical study that included 210 women with diagnosed vaginitis. Patients were divided into two basic groups, women in reproductive period and postmenopausal period. Three subgroups including 30 patients each received one of the three vagitorie formulations for 5 days, after which the effects on subjective and objective symptoms were monitored. Results: Three types of vagitories based on plant extracts had a positive effect in the treatment of vaginitis. Vagitories based on tea tree oil showed better efficiency compared to vagitories with St. John’s wort and vagitories based on extracts of five plants. Women in postmenopausal group reported better tolerability of St. John’s wort-based and five herbs-based vagitories compared to tea tree oil based vagitories. Conclusion: Investigated vagitories showed a positive effect on both objective and subjective symptoms of vagitnis. No serious side effects were reported.
Keywords: calendula; chamomile; tea tree oil; St. John’s wort; vaginal inflammation